Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pengguna Platform Shopee di Surabaya Selatan - Jihan Fauziah Umardi; Iswati Iswati; Anis Fitriyasari (Manajemen Kreatif Jurnal, 2024)
This research was carried out to find out more about the influence of product quality and price on the purchasing decisions of Shopee platform users in South Surabaya, which is in accordance with the main problem raised, namely related to the influence of product quality and price on the purchasing decisions of consumers using Shopee. The background for conducting this research is that in today’s era, of course, quite a few consumers prefer to shop online to make their time and energy more efficient. Also, prices on online e-commerce sites are usually relatively cheaper than shopping directly at physical stores. However, quite a few consumers are still hesitant to shop online because they are worried that the product quality will not meet expectations. The aim of this research is to find out whether there is an influence of product quality and price on purchasing decisions by consumers using Shopee in South Surabaya. Using quantitative research methods which aim to measure the influence between the variables to be studied. Meanwhile, to support this research, samples will be obtained through distributing questionnaires using a measurement scale, namely the Likert scale. The sample collection technique used is a non-probability sampling technique which is purposive sampling, namely a method of taking samples with certain characteristics that have been determined by the researcher. This means that not everyone can be used as a sample by researchers, only those who fit the criteria. The number of the population studied is not yet known, so researchers use the Lemeshow formula to determine the limit for the number of samples to be studied. This research concludes that online shop sellers on the Shopee platform can consider product quality and price, which are related to consumer decisions when making purchases on Shopee.